Catalytic activity of nanosized Au/CeO2 catalyst towards H2O2 decomposition and the role of cationic/metallic ratio in its activity - Abd El-Moemen, Ayman (European Journal of Chemistry, 2019)
The catalytic decomposition of H2O2 on differently pre-treated Au/CeO2 catalyst was studied by kinetic measurements at 20-50 °C. The prepared catalyst was subjected to pre-treatment by heating either in oxidative (10% O2/N2) or inert (pure N2)atmosphere at 400 °C. The different oxidation states of gold were determined by X-ray photoelectron spectroscopy measurements. The Au/CeO2 catalyst exhibited an excellent catalytic activity towards H2O2 decomposition. The catalytic activity of oxygen pre-treated sample was about twice higher than that measured for nitrogen pre-treated sample. This finding ran parallel to the amount of Aun+ as determined by XPS, indicating the role played by Aun+ species as the most active catalyst’s constituent. However, one cannot overlook the role of metallic gold in catalyzing the H2O2, decomposition showing small activity compared to that of cationic gold. The average crystallites size of metallic gold particles was found to be 7±0.5 nm independent of the pre-treatment conditions. The apparent activation energy of the catalyzed reaction was found to be 46.5 and 47.8 kJ/mol for oxygen and nitrogen pre-treatment, respectively.